Professional learning community, trust, and Teacher Professional Development in Malaysian secondary schools - Muhammad Hayat Khan,; Ahmad Zabidi Abdul Razak,; Husaina Banu Kenayathulla, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The professional learning community (PLC) has been shown to nurture a dynamic and positive school culture, where teachers are encouraged to enhance their professional skills and knowledge. This study aimed to identify the levels of PLC, Teacher Professional Development (TPD), and trust among secondary school teachers in Malaysia, as well as determined the relationship between PLC and TPD, PLC and trust, and trust and TPD. Questionnaires were distributed to 272 teachers who were selected using stratified random sampling. Descriptive and inferential statistics were used to analyse the data. Findings show that teachers practice high level of all domains of PLC. The teachers also perceived that they practice high levels of TPD and trust. In addition, there are significant, positive, and weak correlations between all domains of PLC and TPD, as well as TPD and trust. However, there are significant, positive, and strong correlation between all domains of PLC and trust. In conclusion, PLC practices is related to trustful culture in school as well as good professional development among the teachers. The findings implicate that PLC should be encouraged in all teaching institutions to enhance the quality of teaching and learning, as well as the teaching and learning experience for all teachers and students.